Multiple keratocysts of the mandible in association with Gorlin-Goltz syndrome: A rare case report - Gayithri Harish Kulkarni; Shahanavaj I Khaji; Suryakant Metkari; Harish S Kulkarni; Reshma Kulkarni (Wolters Kluwer Medknow Publications, 2014)
Nevoid basal cell carcinoma syndrome is a syndrome with wide variety of manifestations ranging from oral lesions to skeletal deformities. It calls for due responsibility of maxillofacial surgeon to diagnose the syndrome because very often they are the first health professionals to see the patient for the treatment of keratocystic odontogenic tumor. Keratocystic odontogenic tumor has been the topic of numerous investigators, is known for its potentially aggressive behavior, significant rate of recurrences. KCOT often occurs as a solitary lesion, in some instances multiple keratocysts may occur in association with a syndrome called Gorlin-Goltz syndrome (nevoid BCC, jaw cyst bifid rib basal cell nevus syndrome). Here, we present a case of multiple keratocysts in the mandible in association with skeletal, ocular, cutaneous anomalies in the given clinical scenario, which has profound relevance in the clinical dental practice.